A novel and facile liquid whistle hydrodynamic cavitation reactor to produce submicron multiple emulsions. Issue 1 (10th April 2012) - Tang, Siah Ying; Sivakumar, Manickam
<x xml:space="preserve">Abstract</x> Ferrous fumarate, [C4H2FeO4] is widely utilized in the effective treatments and prevention of iron deficiency anemia. But, its administration has been oftentimes linked with quite a few side effects than ferric products. To overcome the side effects, multiple water‐in‐oil‐in‐water (W/O/W) emulsion formulations had been proposed as a new drug delivery system for the controlled release of entrapped active iron compound. In this study, high‐pressure liquid whistle hydrodynamic cavitation reactor has been developed to produce highly stable W/O/W multiple emulsions containing Ferrous Fumarate in submicron scale (∼600 nm) with the droplet‐size distribution polydispersity index in the narrow regime (0.35–0.40). The microscopic observations confirmed that that the physical stability of the W/O/W emulsions was increased significantly with operating pressure and number of emulsification passes. Looking at the potential for scale‐up, this could be a promising technique to produce multiple emulsions incorporated with active constituents. © 2012 American Institute of Chemical Engineers AIChE J, 59: 155–167, 2013